The Structural Basis of Babesia orientalis Lactate Dehydrogenase - Yu, Long; Liu, Qin; Luo, Wanxin; Zhao, Junlong; Alzan, Heba F.; He, Lan (Frontiers in Cellular and Infection Microbiology, 2022)
Glycolytic enzymes play a crucial role in the anaerobic glycolysis of apicomplexan parasites for energy generation. Consequently, they are considered as potential targets for new drug development. Previous studies revealed that lactate dehydrogenase (LDH), a glycolytic enzyme, is a potential drug target in different parasites, such as Plasmodium, Toxoplasma, Cryptosporidium, and Piroplasma. Herein, in order to investigate the structural basis of LDH in Babesia spp., we determined the crystal structure of apo Babesia orientalis (Bo) LDH at 2.67-Å resolution in the space group P1. A five-peptide insertion appears in the active pocket loop of BoLDH to create a larger catalytic pocket, like other protozoa (except for Babesia microti LDH) and unlike its mammalian counterparts, and the absence of this extra insertion inactivates BoLDH. Without ligands, the apo BoLDH takes R-state (relaxed) with the active-site loop open. This feature is obviously different from that of allosteric LDHs in T-state (tense) with the active-site loop open. Compared with allosteric LDHs, the extra salt bridges and hydrogen bonds make the subunit interfaces of BoLDH more stable, and that results in the absence of T-state. Interestingly, BoLDH differs significantly from BmLDH, as it exhibits the ability to adapt quickly to the synthetic co-factor APAD+. In addition, the enzymatic activity of BoLDH was inhibited non-competitively by polyphenolic gossypol with a Ki value of 4.25 μM, indicating that BoLDH is sensitive to the inhibition of gossypol and possibly to its new derivative compounds. The current work provides the structural basis of BoLDH for the first time and suggests further investigation on the LDH structure of other Babesia spp. That knowledge would indeed facilitate the screening and designing of new LDH inhibitors to control the intracellular proliferation of Babesia spp.